2008
DOI: 10.1016/j.biortech.2008.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Predicting anaerobic biogasification potential of ingestates and digestates of a full-scale biogas plant using chemical and biological parameters

Abstract: a b s t r a c tThe aim of this work was to develop simple and fast tests to predict anaerobic biogasification potential (ABP) of ingestates and digestates from a biogas plant. Forty-six samples of both ingestates and digestates were collected within an eight-month observation period and were analyzed in terms of biological and chemical parameters, namely, ABP test, oxygen demand in a 20-h respirometric test (OD20), total solids (TS), volatile solids (VS), total organic carbon (TOC), total Kjeldahl nitrogen (TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(78 citation statements)
references
References 21 publications
4
69
0
5
Order By: Relevance
“…This means that the measurement of the cumulative oxygen uptake rate provided results similar to the biogas test but in a much shorter time (2 d) than the ABP test (60 d) (Schievano et al, 2008), and therefore can be considered an useful and fast test to measure the biological stability in digestates.…”
Section: Biological Stabilitymentioning
confidence: 97%
See 2 more Smart Citations
“…This means that the measurement of the cumulative oxygen uptake rate provided results similar to the biogas test but in a much shorter time (2 d) than the ABP test (60 d) (Schievano et al, 2008), and therefore can be considered an useful and fast test to measure the biological stability in digestates.…”
Section: Biological Stabilitymentioning
confidence: 97%
“…All batches were sealed with Teflon hermetic caps, flushed with an N 2 atmosphere, and incubated at 37 ± 1°C, until no further biogas production was detected (normally around 60 d). More details are reported in Schievano et al (2008).…”
Section: Biological Stability Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha evidenciado una alta variabilidad entre las propuestas metodológicas y experimentales para realizar el ensayo de PBM, al punto de emplear diferentes denominaciones para este ensayo cuando se presentan esquemas metodológicos similares a los que se les realizan cambios mínimos. Se reportan estudios que lo denominan como potencial de metano [4], potencial de bio-metano [7], potencial anaerobio de biogasificación [43] e índice de potencial de metano [44], sin embargo, el término de mayor aceptación y aplicación es el de potencial bioquímico de metano. Esto ha generado confusiones para la implementación del ensayo y dificulta la comparación de los resultados obtenidos en diferentes estudios en los que se emplean sustratos similares.…”
Section: Manométricounclassified
“…Furthermore, Amon et al (2006) showed that dairy manure nutrient composition; specifically crude protein (CP) and lignin concentrations, were significantly related to CH 4 yields from anaerobic digesters. Estimates of manure organic matter composition can also assist in effective bio-based uses of dairy manure, such as biogas and monosugars production, effectively reducing environmental liabilities and providing an economic incentive to dairy producers (Liao et al 2004;Schievano et al 2008). Acid hydrolysis is the typical process used to treat and help convert lignocellulosic materials to sugars, yields of which are significantly related to cellulose, hemicellulose and lignin contents of dairy manure (Liao et al 2005).…”
Section: Introductionmentioning
confidence: 99%